IMPLEMENTATION OF VILLAGE FUNDS FOR COMMUNITY DEVELOPMENT IN SUPPORTING GRASSROOTS - Septi Wulandari; Isna Fitria Agustina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to analyze and evaluate the implementation of village funds for community development in Krembung Village which is adjusted to the rules and planning. This research method is based on qualitative descriptive with purposive sampling techniques. Data collection techniques through interviews, observations, and documentation and analysis starting from reduction, presentation, and drawing conclusions. The results of the study are four dimensions of policy implementation according to Edward III, namely communication, resources, disposition, and bureaucratic structure. Based on the findings of the first dimension, communication, there is still miscommunication between the community and village officials. Second, human resources are an obstacle for villages in utilizing existing village funds, but financial resources are in accordance with other village budget allocations in the implementation of village funds for community development. Third, the disposition based on the reaction theory is good, and the willingness, ability, and commitment of implementers in using village finances for community development. Fourth, the bureaucratic structure, support or preparation of appropriate structures, such as the preparation of positive relationship patterns and in accordance with the responsibilities of each village official.